Role of Immune System Dysfunction in the Pathogenesis of Sepsis: Diagnostic Potentialities - V. K. Kozlov; L. I. Vinnitsky (Общая реаниматология, 2005)
The review deals with a most important problem in reanimatology, namely, the study of the etiology, pathogenesis, laboratory and clinical features, treatment, and prevention of sepsis. It discusses the issues of international terminology, gives the definition of sepsis, outlines the mechanisms responsible for the development of immune system dysfunction in sepsis, and shows the development of multiple organ dysfunction.